Beyond agriculture versus non-agriculture: Decomposing sectoral growth–poverty linkages in five African countries - Dorosh, Paul A.; Thurlow, James (Elsevier, 2018)
Africa’s development debate is often cast as “agriculture versus non-agriculture”, with agriculture’s proponents arguing that agricultural growth is more effective at reducing poverty. This “dual economy” perspective overlooks the heterogeneity within and synergies between these two broad sectors. Recent studies decompose agriculture into subsectors and find that agricultural growth led by smallholder farmers is even more effective at reducing poverty than larger-scale estate farms. In contrast, few studies estimate subsectoral growth–poverty linkages for non-agriculture. Yet we strongly expect, for example, that growth led by informal traders or foreign-owned mining companies will have quite different implications for poverty reduction. Different perspectives on what constitutes “non-agriculture” might therefore explain divergent views on its relative importance for poverty reduction. To address this gap in our understanding, we estimate sectoral poverty–growth elasticities using economy-wide models for five African countries. While our estimated elasticities are higher for agriculture than for non-agriculture as a whole, the extent to which this is true varies considerably across nonagricultural subsectors (and across countries). We find that the poverty–growth elasticities for trade and transport services and manufacturing, especially agro-processing, are often close to, and sometimes exceed, agriculture’s. This means that growth led by these nonagricultural subsectors might be as effective as agriculture at reaching the poor. This confirms the need for a more nuanced treatment of non-agriculture in Africa’s policy debate, and may explain conflicting perspectives on agriculture’s role vis-à-vis non-agriculture.